A method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials

By using AgCuIn near eutectic solder to conduct medium temperature connection under vacuum conditions, the joint strength reduction caused by the difference in thermal expansion coefficient during brazing of zinc sulfide ceramics and titanium alloys is solved, and the joints are maintained at high temperatures, achieving high-strength, heat resistance and long-life joints, meeting the application needs of high-speed aircraft.

CN118060649BActive Publication Date: 2025-04-04HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202410400902.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-04-03
Publication Date
2025-04-04
Estimated Expiration
2044-04-03

AI Technical Summary

Technical Problem

When the zinc sulfide ceramic and titanium alloy are soldered, the residual stress is caused by the difference in thermal expansion coefficient, and the joint strength decreases; and when the high temperature is insulated for a long time, the zinc sulfide grains grow and the infrared transmittance decreases.

Method used

AgCuIn near eutectic solder was used to conduct medium temperature connection under vacuum conditions of 680°C to 760°C. The Cu element in the solder reacted with zinc sulfide ceramics and titanium alloy to form excellent wetting and interface combination, reducing residual stress, and maintaining the heat resistance of the joint at high temperature.

Benefits of technology

It realizes the high-strength, heat resistance and long-life joints of zinc sulfide ceramics and titanium alloys, improves the service capacity of infrared windows, and meets the application needs of high-speed aircraft.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118060649B_ABST
    Figure CN118060649B_ABST
Patent Text Reader

Abstract

A method for brazing zinc sulfide ceramics and titanium alloy dissimilar materials, relates to a method for connecting zinc sulfide ceramics and titanium alloy dissimilar materials. The present invention aims to solve the technical problems that when brazing zinc sulfide ceramic windows and metals, large residual stress is generated due to the difference in thermal expansion coefficients of the two base materials, resulting in a decrease in joint strength, and the infrared transmittance of the zinc sulfide window is reduced when the heat is kept at high temperature for a long time. The present invention uses AgCuIn solder to achieve the connection between zinc sulfide ceramics and titanium alloys under vacuum conditions; the interface between the solder and the base material is well bonded, the weld is dense and has no obvious defects, and the room temperature and high temperature shear properties of the weld are excellent. The present invention can obtain a high temperature resistant joint with excellent mechanical properties, and provides technical support for the application of zinc sulfide ceramics in optical windows.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for connecting zinc sulfide ceramics and titanium alloy dissimilar materials. Background Art

[0002] With the rapid development of national defense and military science and technology, infrared imaging, infrared guidance and other airborne optoelectronic systems are widely used in high-speed aircraft, playing a pivotal role in modern warfare. The infrared window is an important component to ensure the normal operation of these systems. Zinc sulfide ceramics, as an optical functional material, has a wide transmission band (0.35-14 μm), high mechanical strength, and can maintain high optical transmittance at room temperature and high temperature, so that multi-band optoelectronic detection systems can share a window and are not affected by temperature changes during flight. Therefore, zinc sulfide ceramics are currently one of the best choices for infrared window materials for high-speed aircraft. In the process of assembling infrared windows, the reliable sealing of zinc sulfide ceramic windows and metal frames is the key to determining the success of the assembly. In view of the high specific strength, easy processing and high temperature resistance of titanium alloys, they are often used in the aerospace field to make high-strength and lightweight metal frames. However, the current connection process of zinc sulfide ceramics and metals is still in the mechanical connection and bonding stage. The strength and air tightness of the joints obtained by the mechanical connection method are not high, and the thermal shock resistance of the joints obtained by the bonding method is very poor, and long-term use may even cause aging failure. Considering that the maximum operating temperature of zinc sulfide ceramics can reach 600°C, mechanical connection and adhesive methods are difficult to meet the service requirements of infrared windows for high-speed aircraft. Brazing is a mature method for connecting ceramic / metal dissimilar materials, which has the advantages of little impact on the parent material, reliable connection joints, and strong designability of brazing materials. However, there are two challenges when using brazing to manufacture infrared windows: first, the difference in thermal expansion coefficients between zinc sulfide ceramics and titanium alloys will produce large residual stresses, resulting in a decrease in joint strength; second, when kept at high temperature for a long time, the zinc sulfide grains will grow, which can easily reduce the infrared transmittance of the window.

[0003] At present, there is no precedent for the brazing connection between zinc sulfide ceramics and metals, although some studies have achieved the brazing connection between zinc sulfide ceramics and themselves at low temperatures (Zhang S, et al. Wettability and interfacialmorphology of Sn-3.0Ag-0.5Cu solder on electroless nickel plated ZnS transparent ceramic. Journal of Materials Science Materials in Electronics, 2019, 30: 17972-17985; Xu J, et al. Joining ZnS ceramics by using PbTiO 3 -dopedPbO-B 2 O 3 -ZnO.Journal of Materials Science, 2020, 55:8814-8828.), but the poor heat resistance and low connection strength of the joint greatly limit its use under extreme conditions. Therefore, it is necessary to develop brazing materials and brazing methods suitable for new structural parts of zinc sulfide ceramics and titanium alloys to obtain high-strength, heat-resistant and long-life zinc sulfide ceramic / titanium alloy joints, which has important engineering significance for promoting the application of zinc sulfide ceramics in the field of infrared windows. Summary of the invention

[0004] The present invention aims to solve the technical problems that the difference in thermal expansion coefficients of the two base materials during the brazing of zinc sulfide ceramics and metals will produce large residual stress, resulting in a decrease in joint strength, and a decrease in the infrared transmittance of the window during long-term heat preservation at high temperature, and provide a method for brazing dissimilar materials of zinc sulfide ceramics and titanium alloys.

[0005] The method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials of the present invention is carried out according to the following steps:

[0006] 1. Preparation of solder: Pure Ag block, pure Cu block and pure In block are mixed according to the atomic ratio of Ag:Cu:In=53:35:12 and then vacuum arc melted to prepare AgCuIn solder block, and then the AgCuIn solder block is machined into a metal foil with the same size as the surface to be welded of the parent material, and then the metal foil is polished with 600# and 800# metallographic sandpaper in turn until there is no obvious scratch on the surface;

[0007] 2. Pretreatment of the base material: Process the zinc sulfide ceramic base material and the titanium alloy base material to the specified size, and then use diamond grinding paste with a particle size of 2.5μm and 1μm to grind the surface of the zinc sulfide ceramic to be welded to a bright finish; use 600#, 1000# and 2000# metallographic sandpaper to grind the surface of the titanium alloy base material to be welded to a bright finish; put the two polished base materials and the metal foil obtained in step 1 into anhydrous ethanol for ultrasonic cleaning, and blow dry for standby use;

[0008] 3. Assembly of connection samples: Place the cleaned metal foil in step 2 between the zinc sulfide ceramic and the titanium alloy base material, and use an organic binder to fix them into a sandwich structure to obtain the sample to be welded;

[0009] 4. Connection process: Place the sample to be welded assembled in step 3 into a vacuum furnace, place a pressure block on the upper surface of the base material to provide a pressure of 0.1MPa to 0.3MPa, and then perform the following operations under vacuum conditions: heat from room temperature to 300℃ to 320℃ and keep warm for 20min to 25min to volatilize the organic binder, then heat to 680℃ to 760℃ and keep warm for 0 to 20min, then cool to 300℃ to 320℃, and then cool to room temperature with the furnace to obtain a joint.

[0010] The beneficial effects of the present invention are:

[0011] The present invention adopts AgCuIn solder with a near-eutectic composition and a relatively low connection temperature, and realizes the medium-temperature connection of zinc sulfide ceramics and titanium alloys under vacuum conditions of 680°C to 760°C. The AgCuIn near-eutectic solder used in the present invention has excellent plasticity and toughness, good wettability to both zinc sulfide ceramics and titanium alloys, and a melting temperature (680°C) slightly higher than the maximum use temperature (600°C) of the zinc sulfide infrared window, which can effectively alleviate the residual stress caused by the difference in thermal expansion coefficients of the two parent materials, and avoid damage to the light transmittance of zinc sulfide ceramics caused by excessively high temperatures while taking into account the heat resistance of the joint.

[0012] During the brazing process, the Cu element in the brazing filler metal plays a key role in reacting with the parent materials on both sides: on the zinc sulfide ceramic side, the parent material and the brazing filler metal react to form a sulfide layer, which is mainly composed of Cu-S compounds and gradually turns into nano-grains as the brazing temperature rises. The Ti element diffuses from the titanium alloy side to the zinc sulfide ceramic side to participate in the reaction to form black TiS; on the titanium alloy parent material side, a continuous Cu-Ti and Cu-In-Ti compound interface layer is formed between the parent material and the brazing filler metal. At the same time, a eutectic structure dominated by Ag-based and Cu-based solid solutions is generated in the brazing seam. This structure has good plasticity and toughness and a high melting point, which is conducive to the release of residual stress in the joint, and the high temperature resistance is also significantly improved. The average room temperature shear strength of the obtained joint can reach up to 45.2MPa, and the shear strength of the joint at 500°C can reach 33.1MPa.

[0013] The brazed joint of zinc sulfide ceramic and titanium alloy obtained by the method of the present invention can achieve good wetting and interface bonding to the parent material, providing technical support for the manufacture of infrared window connectors that meet the service requirements of high-speed aircraft. BRIEF DESCRIPTION OF THE DRAWINGS

[0014] Figure 1 is a backscattered electron scanning image of the joint obtained in Example 1;

[0015] Figure 2 for Figure 1 A partial enlarged view of the middle area A;

[0016] Figure 3 for Figure 2 Energy spectrum point analysis diagram of the phase at midpoint 1;

[0017] Figure 4 for Figure 2 Energy spectrum point analysis diagram of the phase at midpoint 2;

[0018] Figure 5 for Figure 1 A partial enlarged view of the middle area B;

[0019] Figure 6 for Figure 5 Energy spectrum point analysis diagram of the phase at midpoint 3;

[0020] Figure 7 for Figure 5 Energy spectrum point analysis diagram of the phase at midpoint 4. DETAILED DESCRIPTION

[0021] Specific implementation method 1: This implementation method is a method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials, which is specifically carried out according to the following steps:

[0022] 1. Preparation of solder: Pure Ag block, pure Cu block and pure In block are mixed according to the atomic ratio of Ag:Cu:In=53:35:12 and then vacuum arc melted to prepare AgCuIn solder block, and then the AgCuIn solder block is machined into a metal foil with the same size as the surface to be welded of the parent material, and then the metal foil is polished with 600# and 800# metallographic sandpaper in turn until there is no obvious scratch on the surface;

[0023] 2. Pretreatment of the base material: Process the zinc sulfide ceramic base material and the titanium alloy base material to the specified size, and then use diamond grinding paste with a particle size of 2.5μm and 1μm to grind the surface of the zinc sulfide ceramic to be welded to a bright finish; use 600#, 1000# and 2000# metallographic sandpaper to grind the surface of the titanium alloy base material to be welded to a bright finish; put the two polished base materials and the metal foil obtained in step 1 into anhydrous ethanol for ultrasonic cleaning, and blow dry for standby use;

[0024] 3. Assembly of connection samples: Place the cleaned metal foil in step 2 between the zinc sulfide ceramic and the titanium alloy base material, and use an organic binder to fix them into a sandwich structure to obtain the sample to be welded;

[0025] 4. Connection process: Place the sample to be welded assembled in step 3 into a vacuum furnace, place a pressure block on the upper surface of the base material to provide a pressure of 0.1MPa to 0.3MPa, and then perform the following operations under vacuum conditions: heat from room temperature to 300℃ to 320℃ and keep warm for 20min to 25min to volatilize the organic binder, then heat to 680℃ to 760℃ and keep warm for 0 to 20min, then cool to 300℃ to 320℃, and then cool to room temperature with the furnace to obtain a joint.

[0026] Specific implementation method 2: This implementation method is different from the specific implementation method 1 in that the final thickness of the metal foil after grinding in step 1 is 140 μm to 160 μm. Other aspects are the same as those of the specific implementation method 1.

[0027] Specific implementation method 3: This implementation method is different from specific implementation method 1 or 2 in that: in step 2, ultrasonic cleaning is performed in anhydrous ethanol for 180s to 300s. Other aspects are the same as specific implementation method 1 or 2.

[0028] Specific implementation method 4: This implementation method is different from specific implementation methods 1 to 3 in that the titanium alloy base material described in step 2 is TA15 titanium alloy. The rest is the same as specific implementation methods 1 to 3.

[0029] Specific implementation mode 5: This implementation mode is different from specific implementation mode 4 in that the organic binder described in step 3 is 502 glue. The rest is the same as specific implementation mode 4.

[0030] Specific implementation example 6: This implementation example is different from the specific implementation example 5 in that the pressing block described in step 4 is a tungsten block. The rest is the same as the specific implementation example 5.

[0031] Specific implementation method 7: This implementation method is different from specific implementation method 6 in that: in step 4, the pressure of the block is 0.2 MPa. The rest is the same as specific implementation method 6.

[0032] Specific embodiment eight: This embodiment differs from specific embodiment seven in that the vacuum degree of the entire process in step four is less than or equal to 1×10 -3 Pa. The rest is the same as the seventh embodiment.

[0033] Specific embodiment 9: This embodiment is different from specific embodiment 8 in that: in step 4, the temperature is raised from room temperature to 300° C. and kept at this temperature for 20 minutes to volatilize the organic binder. The rest is the same as specific embodiment 8.

[0034] Specific embodiment 10: This embodiment differs from specific embodiment 9 in that in step 4, the temperature is raised to 700° C. to 740° C. and kept at this temperature for 10 minutes. The rest is the same as specific embodiment 9.

[0035] The present invention is verified by the following examples:

[0036] Example 1: A method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials, specifically carried out according to the following steps:

[0037] 1. Preparation of solder: Pure Ag block, pure Cu block and pure In block were mixed according to the atomic percentage of Ag:Cu:In=53:35:12 and then vacuum arc melted to prepare AgCuIn solder block, and then the AgCuIn solder block was machined into a metal foil with the same size as the surface to be welded of the parent material, and then the metal foil was polished with 600# and 800# metallographic sandpaper in turn until there was no obvious scratch on the surface, and the final thickness was 150μm;

[0038] 2. Pretreatment of the base material: machine the zinc sulfide ceramic base material and the TA15 titanium alloy base material to the specified size, and then use diamond grinding pastes with a particle size of 2.5μm and 1μm to grind the surface of the zinc sulfide ceramic to be welded to a bright finish; use 600#, 1000# and 2000# metallographic sandpaper to grind the surface of the titanium alloy base material to be welded to a bright finish; put the two polished base materials and the metal foil obtained in step 1 into anhydrous ethanol for ultrasonic cleaning for 180s, and blow dry for standby use;

[0039] 3. Assembly of connection samples: Place the cleaned metal foil in step 2 between the zinc sulfide ceramic and the titanium alloy base material, and use organic adhesive 502 glue to fix them into a sandwich structure to obtain the sample to be welded;

[0040] 4. Connection process: Put the sample to be welded assembled in step 3 into a vacuum furnace, place a tungsten block on the upper surface of the base material to provide a pressure of 0.2MPa, and then -4Pa) performs the following operations: heating from room temperature to 300°C at a rate of 15°C / min and keeping the temperature for 20 min to volatilize the organic binder, then heating to the connection temperature of 700°C at a rate of 10°C / min and keeping the temperature for 10 min, then cooling to 300°C at a rate of 5°C / min, and then cooling to room temperature with the furnace to obtain a joint.

[0041] Example 2

[0042] The difference between this embodiment and embodiment 1 is that the connection temperature in step 4 is 720° C. The other steps and parameters are the same as those in embodiment 1.

[0043] Example 3

[0044] The difference between this embodiment and embodiment 1 is that the connection temperature in step 4 is 740° C. The other steps and parameters are the same as those in embodiment 1.

[0045] Example 4

[0046] The difference between this embodiment and embodiment 1 is that the connection temperature in step 4 is 760° C. The other steps and parameters are the same as those in embodiment 1.

[0047] Example 5

[0048] The difference between this embodiment and embodiment 1 is that the connection temperature in step 4 is 720° C. and the temperature is kept for 5 minutes. The other steps and parameters are the same as those in embodiment 1.

[0049] Example 6

[0050] The difference between this embodiment and embodiment 1 is that the connection temperature in step 4 is 720° C. and the temperature is kept for 20 minutes. The other steps and parameters are the same as those in embodiment 1.

[0051] Example 7

[0052] The difference between this embodiment and embodiment 1 is that the connection temperature in step 4 is 720° C. and the temperature is kept for 30 minutes. The other steps and parameters are the same as those in embodiment 1.

[0053] Table 1

[0054]

[0055] Table 1 shows the shear strength test data of the zinc sulfide ceramic / titanium alloy dissimilar material joints obtained in Examples 1 to 7. It can be seen from the table that by using the welding method of the present invention to connect zinc sulfide ceramic and titanium alloy, a welded joint with an average room temperature shear strength of 45.2 MPa can be obtained at most. The shear strength of the joint tested at 500°C is 33.1 MPa.

[0056] Figure 1 This is the backscattered electron scanning image of the joint obtained in Example 1. Area I is the zinc sulfide ceramic base material, area II is the weld, and area III is the TA15 titanium alloy base material. It can be seen that the joint is overall dense and has no defects such as cracks and holes.

[0057] Figure 2 for Figure 1 A partial enlarged view of area A in the middle. Figure 3 for Figure 2 Energy spectrum point analysis diagram of the phase at midpoint 1, Figure 4 for Figure 2 From the energy spectrum point analysis diagram of the phase at midpoint 2, we can see the continuous reaction diffusion layers of Cu-In-S and Cu-S of zinc sulfide ceramic and solder.

[0058] Figure 5 for Figure 1 A partial enlarged view of area B in the middle. Figure 6 for Figure 5 Energy spectrum point analysis diagram of the phase at midpoint 3, Figure 7 for Figure 5 From the energy spectrum point analysis diagram of the phase at midpoint 4, we can see the Cu-Ti and Cu-In-Ti interface reaction layers between TA15 titanium alloy and solder. The metallurgical reaction between the base material and solder on both sides promotes good interface bonding.

Claims

1. A method for brazing zinc sulfide ceramics and titanium alloy dissimilar materials, characterized in that The method for brazing dissimilar materials of zinc sulfide ceramic and titanium alloy is carried out in the following steps:

1. Preparation of solder: Pure Ag block, pure Cu block and pure In block are mixed according to the atomic ratio of Ag:Cu:In=53:35:12 and then vacuum arc melted to prepare AgCuIn solder block, and then the AgCuIn solder block is machined into a metal foil with the same size as the surface to be welded of the parent material, and then the metal foil is polished with 600# and 800# metallographic sandpaper in turn until there is no obvious scratch on the surface; 2. Pretreatment of the base material: Process the zinc sulfide ceramic base material and the titanium alloy base material to the specified size, and then use diamond grinding paste with a particle size of 2.5μm and 1μm to grind the surface of the zinc sulfide ceramic to be welded to a bright finish; use 600#, 1000# and 2000# metallographic sandpaper to grind the surface of the titanium alloy base material to be welded to a bright finish; put the two polished base materials and the metal foil obtained in step 1 into anhydrous ethanol for ultrasonic cleaning, and blow dry for standby use; 3. Assembly of connection samples: Place the cleaned metal foil in step 2 between the zinc sulfide ceramic and the titanium alloy base material, and use an organic binder to fix them into a sandwich structure to obtain the sample to be welded; 4. Connection process: Place the sample to be welded assembled in step 3 into a vacuum furnace, place a pressure block on the upper surface of the base material to provide a pressure of 0.1MPa to 0.3MPa, and then perform the following operations under vacuum conditions: heat from room temperature to 300℃ to 320℃ and keep warm for 20min to 25min to volatilize the organic binder, then heat to 680℃ to 760℃ and keep warm for 0 to 20min, then cool to 300℃ to 320℃, and then cool to room temperature with the furnace to obtain a joint.

2. A method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials according to claim 1, characterized in that The final thickness of the metal foil after grinding in step 1 is 140 μm to 160 μm.

3. A method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials according to claim 1, characterized in that In step 2, ultrasonic cleaning is performed in anhydrous ethanol for 180s to 300s.

4. A method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials according to claim 1, characterized in that The titanium alloy base material described in step 2 is TA15 titanium alloy.

5. A method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials according to claim 1, characterized in that The organic binder described in step three is 502 glue.

6. A method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials according to claim 1, characterized in that The pressing block described in step 4 is a tungsten block.

7. A method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials according to claim 6, characterized in that In step 4, the pressing block provides a pressure of 0.2 MPa.

8. A method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials according to claim 1, characterized in that The vacuum degree of the whole process in step 4 is less than or equal to 1×10 -3 Pa.

9. A method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials according to claim 1, characterized in that In step 4, the temperature is raised from room temperature to 300° C. and kept at this temperature for 20 minutes to volatilize the organic binder.

10. A method for brazing zinc sulfide ceramic and titanium alloy dissimilar materials according to claim 1, characterized in that In step 4, the temperature is raised to 700°C-740°C and kept at this temperature for 10 minutes.

Citation Information

Patent Citations

  • Supersaturated brazing filler metal and preparation method thereof

    CN105345304A

  • Ultrafast laser connection method for transparent ceramic and metal

    CN116768645A